Helping relief campaigns: Social cognitive factors underlying important issues using structural equation modelling - Gholamreza Rasouli; Karim Hamdi (Cogent Business & Management, 2020)
Natural disasters happening around the world have caused a huge burden on local and international charities in recent years. This study tended to examine and explore factors, which cause the migration of people to charitable behaviour based on Bandura's social cognitive theory. By studying the Bandura's social cognitive theory and the research background the conceptual model has been developed. The 199 members of Tehran's Red Crescent Society was selected by stratified sampling and questionnaires were distributed. The validity and reliability of research were confirmed by confirmatory factor analysis and Cronbach's ». The conceptual model was tested using structural equation modelling (SEM). The SEM results showed that perceived self-efficacy, outcome expectancies for donating to disaster campaign and intention to donate to charity has a positive direct effect on intention to donate a disaster campaign. Moreover, news exposure had no significant effect on intention to donate to a disaster campaign. Finally, results revealed that indirect insignificant effect of individualistic explanation of poverty, and awareness of a disaster on intention to donate to disaster campaign. Practical implications and limitations are subsequently discussed in light of the results.
Keywords: 650; donation; social cognitive theory; disaster relief campaigns